Prednisolone-induced Steroid Dependent Nephrotic Syndrome: A Case Report - Johns, Riya; G Joshi, Dharitri; Mathew, Asha (Indian Journal of Pharmacy Practice)
Nephrotic syndrome is a kidney condition that affects the kidney’s glomeruli and causes protein to be excreted in the urine. In paediatric population, the drug of choice for nephrotic syndrome is prednisolone which resolves the signs and symptoms. Prednisolone is a corticosteroid that acts on the immune system to reduce inflammation, swelling, and redness. The International Study of Kidney Disease in Children (ISKDC) proposed a standard initial treatment for children with nephrotic syndrome, consisting of prednisolone therapy for 8 weeks. This case report presents a 4-year-old female patient was presented to the hospital with the complaints of decreased urine output, increased albumin levels (6.8g/dl) and increased protein concentration(15.5mg/m2/day). Tab. Prednisolone (2mg/kg/day) was administered to the patient. After tapering the dose of Prednisolone, the patient again showed proteinuria (400mg/m2/day). Upon restarting the Tab.Prednisolone the urine protein concentration came back to normal levels. Therefore, it is summarized that despite being the first-line drug prednisolone can also cause steroid dependence in patients with nephrotic syndrome. An alternative therapy should be implied along with dose tapering. This implies a wide role for clinical pharmacists in the therapeutic evaluation among paediatric patients.
Keywords: Prednisolone; Nephrotic Syndrome; Steroid Dependent Nephrotic Syndrome; Proteinuria; Tapering of the dose